Proteomic analysis of S-nitrosylated nuclear proteins in rat cortical neurons - Smith, Jacob G. (Sci Signal, 2018)
Neurons modulate gene expression in response to extrinsic signals to enable brain development, cognition, and learning and to process stimuli that regulate systemic physiological functions. This signal-to-gene communication is facilitated by posttranslational modifications such as S-nitrosylation, the covalent attachment of a nitric oxide (NO) moiety to cysteine thiols. In the cerebral cortex, S-nitrosylation of histone deacetylase 2 (HDAC2) is required for gene transcription during neuronal development, but few other nuclear targets of S-nitrosylation have been identified to date. We used S-nitrosothiol resin-assisted capture on NO donor-treated nuclear extracts from rat cortical neurons and identified 614 S-nitrosylated nuclear proteins. Of these, 131 proteins have not previously been shown to be S-nitrosylated in any system, and 555 are previously unidentified targets of S-nitrosylation in neurons. The sites of S-nitrosylation were identified for 59% of the targets, and motifs containing single lysines were found at 33% of these sites. In addition, lysine motifs were necessary for promoting the S-nitrosylation of HDAC2 and methyl-CpG binding protein 3 (MBD3). Moreover, S-nitrosylation of the histone-binding protein RBBP7 was necessary for dendritogenesis of cortical neurons in culture. Together, our findings characterize S-nitrosylated nuclear proteins in neurons and identify S-nitrosylation motifs that may be shared with other targets of NO signaling.